STUDY OF THE CLINICAL CHARACTERISTICS OF SECOND-LINE ART PATIENTS AT A TERTIARY INSTITUTION - Pawan Kakraniya (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: There have been cases of HIV infection and AIDS recorded from almost every nation in the world. Since the discovery of the first case of AIDS, more than 25 million people have died as a result of the pandemic, and 2.5 million children are among the nearly 33.2 million (range 30.6-36.1 million) people living with HIV. Aims & objectives: The current study aimed to examine the clinical profile and relationship between immunosuppression and patient mortality who were receiving second-line ART. Material and Methods: The current investigation was an observational, prospective study carried out at the Department of Medicine. The study lasted two years (from Oct 2018 to Oct 2020). Institutional ethical committee’s prior approval was obtained for the study and protocol. Results: A one-year study including 100 patients who began on second line was conducted. Our study’s most prevalent age range, which made up 52% of the cohort, was 31 to 40. 76 (76%) of the 100 patients under study were men, and 24 (24%) were women. Hemoglobin% significantly improved from the initial value of 11.98 to the subsequent value of 12. (13.27). The clinical T Staging of patients in our study showed that the number of patients in T1 increased from baseline levels of 62% (62 patients) to 78% (78 patients), while the number of patients in T4 decreased from baseline levels of 16% (16 patients) to 8%. Conclusion: Following the start of second-line ART, there has been a significant improvement in CD4 count, clinical T staging of patients, and viral load. Keywords: ART, HIV infection, AIDS pandemic.